please ans trignometry
Attachments:
![](https://hi-static.z-dn.net/files/d28/efc22ec8d5ad6840d5ec809616e81f3a.jpg)
Answers
Answered by
2
Step-by-step explanation:
= (sin²αsin²β + sin²αcos²β + cos²α) + (sin²(2π+α) + cos²(6π-α)+1) / (sin²(π/3 - 4π) + cos²(8π+π/3) + 2)
= [ sin²α(sin²β+cos²β)+cos²α + sin²(2π+α) + cos²(8π-(2π+α) +1 ] / ( sin²(π/3-4π) + cos²(12π-(4π-π/3)) + 2 )
= ( sin²α(1)+cos²α + sin²(2π+α)+cos²(2π+α)+1 )/(sin²(π/3-4π)+cos²(4π-π/3)+2 )
= (1 + 1 + 1)/ ( 1 + 2)
= 3/3
= 1
Similar questions